Analysis Of The Factor Of Language Variation In Village III North Lais - Andi Mudalfy; Missriani Missriani; Siti Rukiyah (Universitas PGRI Palembang, 2023)
The researcher conducted a study entitled factor analysis of language variations, with the aim of being able to describe the results of the factors of the occurrence of language variations in Dusun III Lais Utara, Kec. Lais, Kab. Musi Banyuasin. The research method used is qualitative analysis. Which is the focus point of the problem in this study, namely the factors that occur in language variations. The informants in this study were the people of Dusun III Lais Utara, Kec. Lais, Kab. Musi Banyuasin. The research was conducted in Dusun III Lais Utara, Kec. Lais, Kab. Musi Banyuasin. Data collection techniques used in research are observation, interviews, and recording techniques. So get the results of research by researchers. Researchers get research results, namely the occurrence of a language variation due to two social factors and situational factors. This social factor could be due to environmental factors in Dusun III Lais Utara, Kec. Lais, Kab. Muba. Meanwhile, situational factors consist of language and kinship situations. The results obtained in the language situation when carrying out formal activities, namely meetings, at that time the language situation uses formal language in accordance with the existing situation. In the kinship factor, the occurrence of language variations is because the speakers who speak with the interlocutor both understand the language, so a conversation can occur where the situation will become more intimate at that time the language situation used formal language in accordance with the existing situation. In the kinship factor, the occurrence of language variations is because speakers who speak with the interlocutor both understand the language, so a conversation can occur where the situation will become more intimate at that time the language situation used formal language in accordance with the existing situation. In the kinship factor, the occurrence of language variations is because the speakers who speak with the interlocutor both understand the language, so a conversation can occur where the situation will become more intimate.